Scenario thinking : practical approaches to the future - Wright, George; Cairns, George (Houndmills, Basingstoke, Hampshire, UK : Palgrave MacMillan, 2011)
'Presents new methods in scenario thinking, based on a mix of high-level research and top-level consultancy experience. The authors describe the logical bases of a range of scenario methods and provide detailed'road maps' on how to implement them - together with practical examples of their application'--
Includes bibliographical references (p. 168-172) and index.
Keywords: Business planning; Strategic planning; Decision making; Organizational change